The “auf die Hand” practice: Releasing captives on parole between the Teutonic Order and Lithuania in the end of XIVth and the first half of XVth centuries - Petrilionis, Antanas (Lietuvos istorijos studijos, 2020)
This article presents an analysis of an occurring phrase and practice “auf die Hand” (to one’s hand) and its meaning in the end of the fourteenth and the fifteenth centuries. The main sources for such a study were correspondence between the Teutonic Order’s officers and Lithuania’s rulers, issued documents, and other contemporary written evidence. The “auf die Hand” custom was not just a practice to release captives on parole solely on their own oath, but also on the guarantee of a ruler, officer or another trustworthy person. The captive released on parole or the guarantee promises to return whenever the captor summons him. Also, the guarantor vows that the captive will safely return on a given time. This research shows that the captives with questionable honour may not have been interceded merely for the risk of escaping, because the guarantor, who had also sworn in his honour, would have to compensate for the escaped captive. No doubt such practice was adopted through contact with the Teutonic Order and knights from Western Europe, since we can observe specific features of chivalry: surrender, honour, oaths. Also, it is evident that the meaning behind “auf die Hand” had a semantic connotation – raising a hand to give an oath and giving the captive “to guarantor’s hands.”
Keywords: captives; Teutonic Order; Grand Duchy of Lithuania; oath; guarantee; parole; warfare